2021
DOI: 10.1038/s41598-021-84310-w
|View full text |Cite|
|
Sign up to set email alerts
|

A Model of the Cosmos in the ancient Greek Antikythera Mechanism

Abstract: The Antikythera Mechanism, an ancient Greek astronomical calculator, has challenged researchers since its discovery in 1901. Now split into 82 fragments, only a third of the original survives, including 30 corroded bronze gearwheels. Microfocus X-ray Computed Tomography (X-ray CT) in 2005 decoded the structure of the rear of the machine but the front remained largely unresolved. X-ray CT also revealed inscriptions describing the motions of the Sun, Moon and all five planets known in antiquity and how they were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 14 publications
0
8
0
1
Order By: Relevance
“…A wonderful example of clock with gears is the al-Jazari (1136-1206) elephant clock, [6,7,8]. Although gears have been known for over 2000 years as can be seen in the Antikythera mechanism [9,10,11], whose complexity suggests that gears technology may be even older and could be known in Anatolia and beyond.…”
Section: Early Historymentioning
confidence: 99%
“…A wonderful example of clock with gears is the al-Jazari (1136-1206) elephant clock, [6,7,8]. Although gears have been known for over 2000 years as can be seen in the Antikythera mechanism [9,10,11], whose complexity suggests that gears technology may be even older and could be known in Anatolia and beyond.…”
Section: Early Historymentioning
confidence: 99%
“…The history of computing is believed to have started around 2000 years ago with the Antikythera Mechanism, which was discovered in the sea near Greece in 1901; it is described as a mechanical computer that was used to make astronomical predictions [7]. Computing and calculation machines and methods were also developed in the China, India, and the Islamic worlds prior to, and during, the mediaeval period.…”
Section: The Evolution and Expansion Of Computing And Connectivitymentioning
confidence: 99%
“…The key themes identified in the transcripts are shown in Figure 5 below, which also shows frequency. Aggregation and analysis of qualitative data, generated by responses to all 10 questions, showed that of the 17 themes identified in the transcripts the most common was the environment (identified 15 times), followed by circular/circularity and economic (8); efficiency/energy efficiency (7), social and support (6), awareness, future, manufacture, and public sector (4), growth and market visibility (3), business, green procurement, target, and users (2) and tool (1). Considering the interests (i.e., all bar one have engaged with the CEDaCI project and take part in WGs and CCWs), expertise and roles within the organisations (5 are directly linked to sustainability, 3 are linked to overall efficiency and 1, sustainability-linked research) these results are not surprising; similarly, alignment of the themes with the individual participants reflected the type of organisation with which they work: for example the (A) (who works for a corporate global IT producer) focussed on efficiency, growth, manufacture, and targets; (B) and (E), who work for SMEs specialising in refurbishment/second life products and recycling, focused on the three tenets of sustainability, education, and circularity, as did (C), who also commented on the public sector and works for a national non-profit organisation; (D) and (G) work for a non-profit global open-source IT provider, and both referred to sustainability-linked criteria and the future growth; (F) (who works in a university) focused on the environment and economics as did (H), the technical consultant who also spoke of manufacture and business.…”
Section: Aggregated Data and Trendsmentioning
confidence: 99%
“…Such devices were capable of simple arithmetic calculations by exploiting the continuous nature (mechanical, hydraulic, electrical) of physical systems. One of the earliest examples is the so-called Antikythera mechanism (150-100 BC), a model of the solar system that could predict astronomical positions [16]. Its origin remains uncertain, but more intriguing is the fact that no other computational device of similar complexity was discovered until thousand years later.…”
Section: Computing In a Nutshellmentioning
confidence: 99%